Shikonin attenuates rheumatoid arthritis by targeting SOCS1/JAK/STAT signaling pathway of fibroblast like synoviocytes - Lianhua He; Huijie Luan; Juan He; Miaomiao Zhang; Qingxia Qin; Yiping Hu; Yueming Cai; Desheng Sun; Yu Shi; Qingwen Wang (BMC, 2021)
Abstract Background Rheumatoid arthritis is a progressive and systemic autoimmune disease seriously compromises human health. Fibroblast like synoviocytes are the major effectors of proliferation and inflammation in rheumatoid arthritis synovial tissue. Shikonin has anti-inflammatory and immunomodulatory activities. But, its role on synovitis of rheumatoid arthritis is unknown. Methods The DBA/1 male mice were randomly divided into the following three groups (n = 6): (1) the normal control group of mice, (2) the CIA (collagen-induced arthritis) group in which mice suffered from arthritis induced by collagen, (3) the SKN (shikonin) group of mice which got arthritis and given intragastrically with shikonin 4 mg/kg per day continuously for 20 days,(4) the MTX (methotrexate) group of mice which got arthritis and orally administration with shikonin 0.5  mg/kg once two days continuously for 20 days. The therapeutic effect of shikonin on collagen induced arthritis mice was tested by arthritis incidence rate, arthritis score and inflammatory joint histopathology. The invasion, adhesion and migration of fibroblast like synoviocytes induced by tumor necrosis factor-α were applied to measure the anti-synovitis role of shikonin. The effect of shikonin on expression of interleukin-6, interleukin-1β and tumor necrosis factor-α was measured by enzyme linked immunosorbent assay. The interaction between shikonin and suppressor of cytokine signaling 1 was verified by molecular docking. The signaling pathways activated by shikonin were measured by western blot. Results Shikonin decreased the arthritis score and arthritis incidence, and inhibited inflammation of inflamed joints in collagen induced arthritis mice. And shikonin reduced the number of vimentin+cells in collagen induced arthritis mice inflamed joints. Meanwhile, shikonin suppressed tumor necrosis factor-α-induced invasion, adhesion and migration of fibroblast like synoviocytes and reduced the expression of interleukin-6, interleukin-1β and tumor necrosis factor-α. And we found that shikonin targeted suppressor of cytokine signaling 1. More interestingly, shikonin blocked the phosphorylation of Janus kinase 1/signal transducer andactivator of transcription 1/signal transducer andactivator of transcription 6 in synovial tissues and in fibroblast like synoviocytes. Conclusion Shikonin represents a promising new anti-rheumatoid arthritis drug candidate that has anti-synovitis effect in collagen induced arthritis mice and inhibits tumor necrosis factor-α-induced fibroblast like synoviocytes by targeting suppressor of cytokine signaling 1/ Janus kinase/signal transducer andactivator of transcription signaling pathway. These findings demonstrate that shikonin has anti-synovitis effect and has great potential to be a new drug for the treatment of rheumatoid arthritis.